22Q11.2 deletion syndrome and psychosis: About a case. (13th April 2021) - García-Bernal, C.; Neth, O.; Veguilla, M. Ruiz; Torres, N. Garrido
Abstract : Introduction: We present the case of a boy born in 2002 who was diagnosed with 22q11.2 DS at the age of 2 years. He was referred to neurology at age 9 for "attention deficits and irritability." At age 12 he was referred to mental health for "irritability and anxious and depressive symptoms." The boy was erroneously discharged with a diagnosis of "only" emotional disorder without subsequent follow-up. The evolution of this case resembles the evolution of others already described in the literature. Objectives: To demonstrate the lack of knowledge of the variety of comorbid disorders in this syndrome (20 to 40% present psychotic symptoms). Methods: Bibliographic search in the Pubmed database. Results: There is a partial T-cell immunodeficiency in 22q11.2DS patients confirmed by significantly reduced percentages of circulating T and helper T cells. An increased percentage of Th17 was found in adults with psychotic symptoms compared to non-psychotic adults in one article. The percentage of Th17 was related to the presence of positive psychotic symptoms. Another study says higher levels of IL-17 were found in patients with fewer symptoms. The importance of Th17 and IL-17 in the development of the hippocampus and of Th17 in the development of psychosis is highlighted. In those patients, there is a high IL-6 / IL-10 ratio in favor of a pro-inflammatory state. High levels of IL-6 are correlated with greater neurocognitive deficits and negative symptoms. Conclusions: 1. There is evidence for a theory of inflammation in psychosis development. 2. The 22q11.2 DS could be used as a research model. Disclosure: No significant relationships.